Contested firm governance, institutions and the undertaking of corporate restructuring practices in Germany. (August 2019) - Bhankaraully, Shabneez
This article investigates the undertaking of corporate restructuring practices (employee downsizing and wage moderation) in Germany from 2008 to 2015. The article presents a political perspective that draws on the insights of the power resources approach and of institutional analyses. The theoretical framework highlights how institutional arrangements structure power relations within companies by empowering, in an asymmetrical manner, different categories of firm stakeholders (employees, managers and shareholders) as well as shaping how they relate to each other in an interactive manner. The article's empirical findings point to the importance of extensive, but contingent, corporate restructuring in Germany. Companies are more likely to implement 'defensive' corporate restructuring practices under conditions of high leverage/debt than when confronted by shareholder value driven investors, thereby reflecting the presence of overlapping interests between employees and managers.